2010
DOI: 10.1002/jcb.22477
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular‐regulated kinase—mitogen‐activated protein kinase cascade: Unsolved issues

Abstract: This review point out several aspects regarding the mitogen-activated protein kinase (MAPK)/extracellular-regulated kinase (Erk) network, which are still pending issues in the understanding how this pathway integrate information to drive cell fates. Focusing on the role of Erk during cell cycle, it has to be underlined that Erk downstream effectors, which are required for mitosis progression and contribute to aneuploidy during tumorigenesis, remain to be determined. In addition to the identity of the terminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 47 publications
0
34
0
Order By: Relevance
“…Upon stimulation, phosphorylation of the ERK TEY domain releases ERK and allows phosphorylation of its NTS by CK2 and active ERK to generate a negatively charged patch in ERK, binding to importin 7 and nuclear translocation. These results provide an important role of CK2 in regulating nuclear ERK activities.Extracellular signal-regulated kinases (ERK) 1 and 2 (ERK1/2) are central signaling proteins that mediate a variety of vital cellular processes, including proliferation, survival, and even apoptosis (1,4,15,29,50). In order to execute their functions, ERK molecules activate a large number of regulatory proteins, which are localized either in the cytoplasm or within various organelles, including mainly the nucleus (52).…”
mentioning
confidence: 99%
“…Upon stimulation, phosphorylation of the ERK TEY domain releases ERK and allows phosphorylation of its NTS by CK2 and active ERK to generate a negatively charged patch in ERK, binding to importin 7 and nuclear translocation. These results provide an important role of CK2 in regulating nuclear ERK activities.Extracellular signal-regulated kinases (ERK) 1 and 2 (ERK1/2) are central signaling proteins that mediate a variety of vital cellular processes, including proliferation, survival, and even apoptosis (1,4,15,29,50). In order to execute their functions, ERK molecules activate a large number of regulatory proteins, which are localized either in the cytoplasm or within various organelles, including mainly the nucleus (52).…”
mentioning
confidence: 99%
“…The known substrate for MEK1/2 is ERK1/2 (7). The role of ERK activity during G 2 /M transition is not well understood, but ERK seems to function through a complex and indirect role on a small subset of G 2 /M phosphoproteins (55), and the downstream effectors of ERK, which are required for mitosis progression, remain to be determined (2). However, a specific inhibitor of ERK1/2 (FR180204) had no influence on the titers of either the passaged mutants or wild-type PrV.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we first evaluated the effect of increased CD147 on the activation status of Ras in MCF-10A cells because Ras is frequently upstream of ERK activation (39). We found that up-regulation of CD147 led to a ϳ1.5-2-fold increase in Ras activation, measured as an increased proportion of Ras-bound GTP, as well as a concomitant increase in phosphorylated ERK (p-ERK) (Fig.…”
Section: Up-regulation Of Cd147 Induces Activation Of Egfr-ras-erk Simentioning
confidence: 99%